RAPID UREASE TEST POSITIVITY BY ENDOSCOPY IN ADULT PATIENTS WITH DYSPEPSIA IN A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Dr . Deepak; Dr. Pankaj Kumar; Kumar, Dr . Manish; Dr. Ranjeet K Sinha; Dr . Amit Kumar; Dr . Saurav Raj (Student’s Journal of Health Research Africa, 2024)
Background Dyspepsia, a common gastrointestinal complaint among adults, necessitates efficient diagnostic methods for tailored treatment. The Rapid Urease Test (RUT) during endoscopy offers a cost-effective and prompt approach to identifying H. pylori infection, a prevalent cause of gastritis. This study evaluates the diagnostic value and clinical utility of RUT in adults with dyspepsia. Methods A cross-sectional study was conducted, enrolling 500 adult patients undergoing upper gastrointestinal tract endoscopy. Demographic data, indications for endoscopy, and endoscopic findings were collected. The RUT was performed using the RUT Test kit. Random positive samples were subjected to histopathological examination to see the accuracy of the kit and the significance of test accuracy was judged by statistical analyses. Results In this study of 500 adult dyspeptic patients, a gender distribution (54% vs 46%) with a preponderance of rural background (66.7%) was observed. Common indications for endoscopy were pain abdomen, RUQ pain, and epigastric burning, with multifocal and mild antral gastritis being predominant endoscopic findings providing insights into dyspepsia and diagnostic methods. Other notable findings included esophageal and duodenal abnormalities, a history of hepatitis (25.6%), and chronic liver disease (15.5%). H. pylori infection was detected in 32.4% of cases on RUT. Sedation was administered in 39.1% of cases. Conclusion The RUT during endoscopy is a valuable diagnostic tool for H. pylori-associated gastritis in dyspeptic patients. Its high sensitivity and specificity enable prompt and early targeted therapy for better outcomes. RUT during endoscopy for dyspeptic patients should be considered, especially in populations with a high prevalence of H. pylori infection. Recommendations The study highlights the effectiveness of the RUT for diagnosing H. pylori in dyspeptic patients during endoscopy. Given its accuracy and cost-effectiveness, RUT is recommended for routine use in regions with high H. pylori prevalence.